Neuroscience and Exercise: An Indicator of Health and Learning in the Educational Context [Neurociencia y Ejercicio: Un Indicador de Salud y Aprendizaje en el Contexto Educativo] - Toro-Arevalo, S (Universidad Nacional de Colombia, 2019)
In recent years, neuroscience has shown the particular and global benefits of exercise and active life in the health of students. They enrich neural networks, plasticity and pro-duction of neurotransmitters that favour different domains of human behavior and con-dition. In this context, the objective of this essay is to dialogue based on the importance of an active life in the educational field and a discipline that not only plays a role at the brain or morphofunctional level, but rather multidimensional, which emerges from the molecular level, cellular, cerebral, systemic, psychological and social. Because of this, one of the main conclusions is related to the students’ possibility of having the ability to understand and reflect processes that enable learning according their own life, as an harmonic continuum between organicity and culture and between life and language. © 2019, Universidad Nacional de Colombia. All rights reserved.